Recombinant Production of Bovine αS1-Casein in Genome-Reduced Bacillus subtilis Strain IIG-Bs-20-5-1 - Lennart Biermann; Lea Rahel Tadele; Elvio Henrique Benatto Perino; Reed Nicholson; Lars Lilge; Rudolf Hausmann (Microorganisms)
Background: Cow’s milk represents an important protein source. Here, especially casein proteins are important components, which might be a promising source of alternative protein production by microbial expression systems. Nevertheless, caseins are difficult-to-produce proteins, making heterologous production challenging. However, the potential of genome-reduced Bacillus subtilis was applied for the recombinant production of bovine αS1-casein protein. Methods: A plasmid-based gene expression system was established in B. subtilis allowing the production of his-tagged codon-optimized bovine αS1-casein. Upscaling in a fed-batch bioreactor system for high cell-density fermentation processes allowed for efficient recombinant αS1-casein production. After increasing the molecular abundance of the recombinant αS1-casein protein using immobilized metal affinity chromatography, zeta potential and particle size distribution were determined in comparison to native bovine αS1-casein. Results: Non-sporulating B. subtilis strain BMV9 and genome-reduced B. subtilis strain IIG-Bs-20-5-1 were applied for recombinant αS1-casein production. Casein was detectable only in the insoluble protein fraction of the genome-reduced B. subtilis strain. Subsequent high cell-density fed-batch bioreactor cultivations using strain IIG-Bs-20-5-1 resulted in a volumetric casein titer of 56.9 mg/L and a yield of 1.6 mgcasein/gCDW after reducing the B. subtilis protein content. Comparative analyses of zeta potential and particle size between pre-cleaned recombinant and native αS1-casein showed pH-mediated differences in aggregation behavior. Conclusions: The study demonstrates the potential of B. subtilis for the recombinant production of bovine αS1-casein and underlines the potential of genome reduction for the bioproduction of difficult-to-produce proteins.